Resin-based ceramic composite material as well as preparation method and application thereof

A resin-based ceramic composite material with boron nitride nanosheets and ceramic materials enhances mechanical properties, addressing low strength issues in traditional composites for dental applications.

CN119185078APending Publication Date: 2024-12-27任光辉 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411200121.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Traditional resin-based ceramic composite materials suffer from low strength, which limits their application in tooth restoration due to brittleness and mismatched mechanical properties with human teeth.

Method used

A resin-based ceramic composite material comprising boron nitride nanosheets, ceramic materials, and a resin matrix, with specific mass percentages and properties, enhancing mechanical properties like bending strength, hardness, and fracture toughness.

Benefits of technology

The composite material achieves bending strength and hardness similar to human enamel, improving durability and suitability for dental applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to a resin-based ceramic composite material as well as a preparation method and application thereof. The resin-based ceramic composite material comprises a boron nitride nanosheet, a ceramic material and a resin matrix, based on the mass of the resin-based ceramic composite material, the mass percent of the boron nitride nanosheet is 0.1%-1%, the mass percent of the ceramic material is 82%-83%, and the mass percent of the resin matrix is 16%-17.9%, so that the bending strength and hardness of the resin-based ceramic composite material are effectively improved, and the resin-based ceramic composite material can be applied to the oral environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of dental materials, and in particular to a resin-based ceramic composite material and a preparation method and application thereof. Background Art

[0002] There are many kinds of materials used to make indirect restorations in clinical practice. For example, metal materials were used in the early days. However, due to the poor aesthetic properties of metal materials, they were gradually replaced by ceramic materials. Ceramics have become the main restorative materials due to their good aesthetic properties, color stability and biocompatibility. At present, ceramic restorations are indispensable in mimicking the structure and physical properties of the dentition, but the brittleness of ceramic materials is still their inherent weakness, and ceramic materials have higher elastic modulus and hardness than the opposing teeth, which damages the health of the opposing teeth.

[0003] In order to solve the problems of ceramic materials, composite materials have emerged. Resin-based ceramic composite materials are a type of composite materials. They have acceptable mechanical properties as well as good biological and aesthetic properties. In addition, they do not require sintering during the production process, saving time and attracting more and more attention from clinicians. However, traditional resin-based ceramics have the problem of low strength, which limits their application in tooth restoration. Summary of the invention

[0004] The present application provides a resin-based ceramic composite material and a preparation method and application thereof, so as to improve the bending strength and hardness of the resin-based ceramic composite material so that it can be used in an oral environment.

[0005] In a first aspect of the present application, a resin-based ceramic composite material is provided, comprising boron nitride nanosheets, a ceramic material and a resin matrix; based on the mass of the resin-based ceramic composite material, the mass percentage of the boron nitride nanosheets is 0.1% to 1%, the mass percentage of the ceramic material is 82% to 83%, and the mass percentage of the resin matrix is ​​16% to 17.9%.

[0006] In some embodiments, based on the mass of the resin-based ceramic composite material, the mass percentage of the boron nitride nanosheets is 0.3% to 0.9%.

[0007] In some embodiments, the average diameter of the boron nitride nanosheets is 0.1 μm to 0.4 μm.

[0008] In some embodiments, the ceramic material includes at least one of barium glass powder and silanized barium glass powder.

[0009] In some embodiments, the average particle size of the ceramic material is 0.7 μm to 3 μm.

[0010] In some embodiments, the resin matrix includes at least two of bisphenol A glycerol dimethacrylate, triethylene glycol dimethacrylate, methacrylate, and urethane dimethacrylate.

[0011] In some embodiments, the resin matrix includes triethylene glycol dimethacrylate and urethane dimethacrylate, and the mass ratio of triethylene glycol dimethacrylate to urethane dimethacrylate is (7-3): (3-7).

[0012] In some embodiments, the flexural strength of the resin-based ceramic composite material is ≥209 MPa.

[0013] In some embodiments, the flexural strength of the resin-based ceramic composite material is 209 MPa to 245 MPa.

[0014] In some embodiments, the fracture toughness of the resin-based ceramic composite material is 1.25 MPa·m 1 / 2 ~2.05MPa·m 1 / 2 .

[0015] In some embodiments, the Vickers hardness of the resin-based ceramic composite material is ≥103 HV.

[0016] In some embodiments, the Vickers hardness of the resin-based ceramic composite material is 103HV~125HV.

[0017] In a second aspect of the present application, a method for preparing a resin-based ceramic composite material is provided, comprising the following steps:

[0018] The boron nitride nanosheets, ceramic materials, initiators and resin monomers are mixed and subjected to dry pressing to obtain an intermediate;

[0019] The intermediate is cured so that the resin monomer forms a resin matrix to obtain a resin-based ceramic composite material; the resin-based ceramic composite material includes the boron nitride nanosheets, the ceramic material and the resin matrix; based on the mass of the resin-based ceramic composite material, the mass percentage of the boron nitride nanosheets is 0.1% to 1%, the mass percentage of the ceramic material is 82% to 83%, and the mass percentage of the resin matrix is ​​16% to 17.9%.

[0020] In some embodiments, the mass of the initiator is 0.1 wt % to 0.5 wt % of the mass of the resin monomer.

[0021] In some embodiments, the initiator includes one or more of a peroxide initiator and an azo compound initiator.

[0022] In some embodiments, the dry pressing process includes a compression molding process, and the process conditions of the compression molding process include: the compression molding pressure is 10 MPa to 20 MPa.

[0023] In some embodiments, the process conditions of the curing treatment include: a curing temperature of 80° C. to 140° C. and a curing time of 7 h to 12 h.

[0024] In some embodiments, the step of mixing the boron nitride nanosheets, the ceramic material, the initiator and the resin monomer comprises: mixing the boron nitride nanosheets, the ceramic material, the initiator, the resin monomer and the solvent by ball milling, wherein the solvent comprises an alcohol solvent.

[0025] In some embodiments, before the step of mixing the boron nitride nanosheets, ceramic material, initiator and resin monomer, the step further includes: dispersing and pre-drying the boron nitride raw material to obtain the boron nitride nanosheets, wherein the dispersing treatment includes at least one of ball milling and ultrasonic treatment.

[0026] The third aspect of the present application provides the use of at least one of the resin-based ceramic composite material described in the first aspect of the present application and the resin-based ceramic composite material prepared by the preparation method described in the second aspect of the present application in the preparation of dental restoration products.

[0027] Compared with traditional technologies, the above resin-based ceramic composite materials have at least the following advantages:

[0028] The ceramic material in the above-mentioned resin-based ceramic composite material can be embedded in the resin matrix, so that the composite material can combine the advantages of the ceramic material and the resin matrix, and has good mechanical properties and biological properties. The thermal stability and chemical stability of the boron nitride nanosheets are relatively good, and they have high strength and elastic modulus. The boron nitride nanosheets, ceramic materials and resin matrix are used together, and the mass percentages of the three in the resin-based ceramic composite material are controlled within a reasonable range, which can effectively improve the bending strength, hardness and fracture toughness of the resin-based ceramic composite material. The above-mentioned resin-based ceramic composite material is easy to cut by CAD / CAM, has a bending strength, hardness and fracture toughness similar to that of human enamel, and can be used in the oral environment. DETAILED DESCRIPTION

[0029] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.

[0030] In this application, "first aspect", "second aspect", "third aspect", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0031] In this application, "optionally", "optional", and "optional" mean optional or dispensable, that is, any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.

[0032] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0033] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0034] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as those commonly understood by technicians in the technical field of this application. The terms used in this application and in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used in this application includes any and all combinations of one or more related listed items. The term "multiple" in this application means at least two, such as two, three, etc., unless otherwise clearly and specifically limited.

[0035] An embodiment of the present application provides a resin-based ceramic composite material, including boron nitride nanosheets, a ceramic material and a resin matrix; based on the mass of the resin-based ceramic composite material, the mass percentage of the boron nitride nanosheets is 0.1%~1%, the mass percentage of the ceramic material is 82%~83%, and the mass percentage of the resin matrix is ​​16%~17.9%.

[0036] The ceramic material in the above-mentioned resin-based ceramic composite material can be embedded in the resin matrix, so that the composite material can combine the advantages of the ceramic material and the resin matrix, and has good mechanical properties and biological properties. The thermal stability and chemical stability of the boron nitride nanosheets are relatively good, and they have high strength and elastic modulus. The boron nitride nanosheets, ceramic materials and resin matrix are used together, and the mass percentages of the three in the resin-based ceramic composite material are controlled within a reasonable range, which can effectively improve the bending strength, hardness and fracture toughness of the resin-based ceramic composite material. The above-mentioned resin-based ceramic composite material is easy to cut by CAD / CAM, has a bending strength, hardness and fracture toughness similar to that of human enamel, and can be used in the oral environment.

[0037] When the mass percentage of boron nitride nanosheets in the above-mentioned resin-based ceramic composite material is too low, the improvement of the bending strength, hardness and fracture toughness of the resin-based ceramic composite material is not obvious; when the mass percentage of boron nitride nanosheets in the above-mentioned resin-based ceramic composite material is too high, the boron nitride nanosheets are easy to agglomerate, resulting in a significant decrease in the bending strength, hardness and fracture toughness of the resin-based ceramic composite material.

[0038] Specifically, the mass percentage of boron nitride nanosheets includes but is not limited to: 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or a range between any two of the foregoing; the mass percentage of ceramic material includes but is not limited to: 82%, 82.1%, 82.2%, 82.3%, 82.4%, 82.5%, 82.6%, 82.7%, 82.8%, 82.9%, 83% or a range between any two of the foregoing; the mass percentage of resin matrix includes but is not limited to: 16%, 16.2%, 16.4%, 16.6%, 16.8%, 17%, 17.2%, 17.4%, 17.6%, 17.9% or a range between any two of the foregoing.

[0039] In some embodiments, based on the mass of the resin-based ceramic composite material, the mass percentage of the boron nitride nanosheets is 0.3% to 0.9%. Controlling the mass percentage of the boron nitride nanosheets within the above range is conducive to further improving the bending strength, hardness and fracture toughness of the resin-based ceramic composite material.

[0040] In some embodiments, the average diameter of the boron nitride nanosheets is 0.1 μm to 0.4 μm. By controlling the average diameter of the boron nitride nanosheets within the above range, the dispersion effect of the boron nitride nanosheets in the resin-based ceramic composite material can be improved, which is conducive to further improving the bending strength and hardness of the resin-based ceramic composite material.

[0041] In some embodiments, the ceramic material includes at least one of barium glass powder and silanized barium glass powder. The above-mentioned types of ceramic materials can be better dispersed in the solvent, thereby enhancing the cross-linking effect between the resin matrix and the ceramic material, which is more conducive to improving the bending strength of the resin-based composite material.

[0042] In some embodiments, the average particle size of the ceramic material is 0.7 μm to 3 μm. Specifically, the average particle size of the ceramic material includes but is not limited to: 0.7 μm, 1 μm, 1.2 μm, 1.5 μm, 1.7 μm, 2 μm, 2.2 μm, 2.5 μm, 2.7 μm, 3 μm or a range between any two of the foregoing.

[0043] In some embodiments, the resin matrix includes at least two of bisphenol A glycerol dimethacrylate (BisGMA), triethylene glycol dimethacrylate (TEGDMA), methacrylate (MMA) and urethane dimethacrylate (UDMA). Selecting the above types of resin matrices is more conducive to enhancing the flexural strength of the resin-based ceramic composite material.

[0044] In some embodiments, the resin matrix includes triethylene glycol dimethacrylate and urethane dimethacrylate, and the mass ratio of triethylene glycol dimethacrylate to urethane dimethacrylate is (7-3): (3-7). The above-mentioned types and mass ratios of resin matrices are used in combination to provide a higher bending strength for the resin-based ceramic composite material. Specifically, the mass ratio of triethylene glycol dimethacrylate to urethane dimethacrylate includes but is not limited to: 7:3, 7:4, 7:5, 7:6, 7:7, 6:7, 5:7, 4:7, 3:7 or a range between any two of the foregoing.

[0045] In some embodiments, the flexural strength of the resin-based ceramic composite material is ≥ 209 MPa. Specifically, the flexural strength of the resin-based ceramic composite material includes, but is not limited to, 209 MPa, 210 MPa, 215 MPa, 220 MPa, 225 MPa, 230 MPa, 235 MPa, 240 MPa, 245 MPa, 250 MPa, or a range between any two of the foregoing.

[0046] In some embodiments, the flexural strength of the resin-based ceramic composite material is 209 MPa to 245 MPa.

[0047] In some embodiments, the fracture toughness of the resin-based ceramic composite material is 1.25 MPa·m 1 / 2 ~2.05MPa·m 1 / 2 Specifically, the fracture toughness of the resin-based ceramic composite material includes but is not limited to: 1.25 MPa·m 1 / 2 , 1.3MPa·m1 / 2 , 1.4MPa·m 1 / 2 , 1.5MPa·m 1 / 2 , 1.6MPa·m 1 / 2 , 1.7MPa·m 1 / 2 , 1.8MPa·m 1 / 2 , 1.9MPa·m 1 / 2 , 2MPa·m 1 / 2 , 2.05MPa·m 1 / 2 Or a range between any two of the foregoing.

[0048] In some embodiments, the Vickers hardness of the resin-based ceramic composite material is ≥ 103 HV. Specifically, the Vickers hardness of the resin-based ceramic composite material includes but is not limited to: 103 HV, 105 HV, 110 HV, 115 HV, 120 HV, 125 HV, 130 HV or a range between any two of the foregoing.

[0049] In some embodiments, the Vickers hardness of the resin-based ceramic composite material is 103 HV to 125 HV.

[0050] Another embodiment of the present application provides a method for preparing a resin-based ceramic composite material, comprising the following steps:

[0051] The boron nitride nanosheets, ceramic materials, initiators and resin monomers are mixed and subjected to dry pressing to obtain an intermediate;

[0052] The intermediate is cured so that the resin monomer forms a resin matrix to obtain a resin-based ceramic composite material; the resin-based ceramic composite material includes boron nitride nanosheets, a ceramic material and a resin matrix; based on the mass of the resin-based ceramic composite material, the mass percentage of the boron nitride nanosheets is 0.1% to 1%, the mass percentage of the ceramic material is 82% to 83%, and the mass percentage of the resin matrix is ​​16% to 17.9%.

[0053] The ceramic material in the resin-based ceramic composite material obtained by the above preparation method can be embedded in the resin matrix, so that the composite material can combine the advantages of the ceramic material and the resin matrix, and has good mechanical properties and biological properties. The thermal stability and chemical stability of the boron nitride nanosheets are relatively good, and it has high strength and elastic modulus. The boron nitride nanosheets, ceramic materials and resin matrix are used in combination, and the mass percentages of the three in the resin-based ceramic composite material are controlled within a reasonable range, which can effectively improve the bending strength, hardness and fracture toughness of the resin-based ceramic composite material. The above resin-based ceramic composite material is easy to CAD / CAM cutting, has bending strength, hardness and fracture toughness similar to human enamel, and can be used in oral environments. The above preparation method is relatively simple, which is conducive to the large-scale production of resin-based ceramic composite materials.

[0054] In some embodiments, the mass of the initiator is 0.1 wt% to 0.5 wt% of the mass of the resin monomer. Specifically, the mass of the initiator can be 0.1 wt%, 0.15 wt%, 0.2 wt%, 0.25 wt%, 0.3 wt%, 0.35 wt%, 0.4 wt%, 0.45 wt%, 0.5 wt% of the mass of the resin monomer, or a range between any two of the foregoing.

[0055] In some embodiments, the initiator includes one or more of a peroxide initiator and an azo compound initiator.

[0056] In some embodiments, the peroxide initiator includes benzoyl peroxide.

[0057] In some embodiments, the azo compound initiator includes azobisisobutyronitrile (AIBN).

[0058] In some embodiments, the dry pressing process includes compression molding, and the process conditions of the compression molding process include: the compression molding pressure is 10MPa to 20MPa. Specifically, the compression molding pressure includes but is not limited to: 10MPa, 11MPa, 12MPa, 13MPa, 14MPa, 15MPa, 16MPa, 17MPa, 18MPa, 19MPa, 20MPa or a range between any two of the foregoing.

[0059] In some embodiments, the process conditions of the curing treatment include: a curing temperature of 80°C to 140°C, and a curing time of 7h to 12h. Controlling the curing temperature and curing time within the above range is conducive to sufficient cross-linking of the resin monomer. Specifically, the curing temperature includes but is not limited to: 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C or a range between any two of the foregoing; the curing time includes but is not limited to: 7h, 8h, 9h, 10h, 11h, 12h or a range between any two of the foregoing.

[0060] In some embodiments, the step of mixing boron nitride nanosheets, ceramic materials, initiators, and resin monomers includes: mixing boron nitride nanosheets, ceramic materials, initiators, resin monomers, and solvents by ball milling, and the solvent includes an alcohol solvent. In some embodiments, before the dry pressing molding process, it also includes: drying and grinding the solution obtained by ball milling in sequence. Optionally, the drying temperature is 50°C to 60°C, and the drying time is 12h to 24h. In some embodiments, the alcohol solvent includes at least one of ethanol, n-propanol, and isopropanol.

[0061] In some embodiments, the step of mixing the boron nitride nanosheets, the ceramic material, the initiator and the resin monomer comprises: mixing the initiator and the resin monomer using an ultrasonic method, and then mixing them with the boron nitride nanosheets and the ceramic material. For example, then mixing them with the boron nitride nanosheets and the ceramic material by ball milling. In some embodiments, the process conditions of ultrasonic mixing include: the ultrasonic time is 30min to 90min.

[0062] In some embodiments, the material of the ball mill jar used in the ball milling process includes one or more of zirconium oxide, polyurethane and polyethylene.

[0063] In some embodiments, the grinding balls used in the ball milling process include at least one of agate grinding balls and zirconia grinding balls.

[0064] In some embodiments, before the step of mixing the boron nitride nanosheets, the ceramic material, the initiator and the resin monomer, the step of dispersing and pre-drying the boron nitride raw material to obtain the boron nitride nanosheets is further included, wherein the dispersing treatment includes at least one of a ball milling method and an ultrasonic method. Optionally, the average sheet diameter of the boron nitride nanosheets is 0.1 μm to 0.4 μm.

[0065] In some embodiments, the step of dispersing the boron nitride raw material includes: pre-milling the boron nitride raw material and the pre-milling solvent, and the process conditions of the pre-milling include: the ball milling speed is 600r / min~800r / min, and the ball milling time is 1h~2h. Specifically, the ball milling speed includes but is not limited to: 600r / min, 630r / min, 650r / min, 680r / min, 700r / min, 720r / min, 750r / min, 780r / min, 800r / min or the range between any two of the foregoing; the ball milling time includes but is not limited to: 1h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2h or the range between any two of the foregoing.

[0066] In some embodiments, the pre-milling solvent includes an alcohol solvent. Optionally, the alcohol solvent includes at least one of ethanol, n-propanol and isopropanol.

[0067] In some embodiments, the steps of dispersing and pre-drying the boron nitride raw material include: ultrasonically vibrating the solution obtained by the dispersion for 3 hours to 4 hours, and taking the supernatant for pre-drying after standing. Optionally, the pre-drying temperature can be 50° C. and the pre-drying time can be 12 hours.

[0068] By adjusting the process conditions of the above-mentioned preparation method, the resin-based ceramic composite material in one embodiment of the present application can be obtained.

[0069] Another embodiment of the present application provides the use of at least one of the resin-based ceramic composite material and the resin-based ceramic composite material prepared by the preparation method in the present application in the preparation of dental restoration products. The dental restoration products include but are not limited to: all-ceramic crown restorations, partial crown restorations, inlays, veneers, and high onlays. The all-ceramic crown restoration is not easy to break when chewed by the patient, and the resin-based ceramic composite material can reduce the stress concentration of the abutment and the crown itself.

[0070] In order to further illustrate the present application, the technical scheme of the present application is described in detail below in conjunction with specific examples. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in the field or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0071] Example 1

[0072] A method for preparing a resin-based ceramic composite material comprises the following steps:

[0073] (1) Putting boron nitride raw material in a ball mill, adding pre-milling solvent anhydrous ethanol, and pre-milling in a ball mill at 600 r / min for 1 hour, pouring the obtained solution into a beaker, and then dispersing it in an ultrasonic disperser for 3 hours and standing at room temperature for 24 hours, extracting the supernatant with a needle tube, placing it in a 50°C oven for 12 hours, taking it out, grinding and crushing, and obtaining boron nitride nanosheets with an average sheet diameter of 0.3 μm;

[0074] (2) adding the above-mentioned boron nitride nanosheets, barium glass powder (ceramic material) with an average particle size of 0.7 μm, and a resin monomer containing an initiator (the resin monomer is composed of dimethacrylate urethane and dimethacrylate triethylene glycol in a mass ratio of 7:3) into a ball mill according to a mass ratio of 0.3:97:25; the mass of the initiator is 0.2 wt %; ball milling is performed with anhydrous ethanol as a solvent for 30 min, and then placed in an oven at 50° C. for 12 h, taken out, ground and crushed to obtain a powder, and the powder is molded at a pressure of 10 MPa to obtain an intermediate;

[0075] (3) The intermediate is placed in an oven at 120° C. for curing for 12 hours to form a resin matrix, thereby obtaining a resin-based ceramic composite material; based on the mass of the resin-based ceramic composite material, the mass percentage of the boron nitride nanosheets is 0.25%, the mass percentage of the ceramic material is 79.31%, and the mass percentage of the resin matrix is ​​20.44%.

[0076] Example 2

[0077] The preparation method of the resin-based ceramic composite material is basically the same as that of Example 1, except that: in step (2), the boron nitride nanosheets, the barium glass powder (ceramic material) with an average particle size of 0.7 μm, and the resin monomer containing an initiator (the resin monomer is composed of urethane dimethacrylate and triethylene glycol dimethacrylate in a mass ratio of 7:3) are added to a ball mill in a mass ratio of 0.5:97:25;

[0078] In step (3), based on the mass of the resin-based ceramic composite material, the mass percentage of the boron nitride nanosheets is 0.41%, the mass percentage of the ceramic material is 79.18%, and the mass percentage of the resin matrix is ​​20.41%.

[0079] Example 3

[0080] The preparation method of the resin-based ceramic composite material is basically the same as that of Example 1, except that: in step (2), the boron nitride nanosheets, the barium glass powder (ceramic material) with an average particle size of 0.7 μm, and the resin monomer containing an initiator (the resin monomer is composed of urethane dimethacrylate and triethylene glycol dimethacrylate in a mass ratio of 7:3) are added to a ball mill in a mass ratio of 0.7:97:25;

[0081] In step (3), based on the mass of the resin-based ceramic composite material, the mass percentage of the boron nitride nanosheets is 0.57%, the mass percentage of the ceramic material is 79.05%, and the mass percentage of the resin matrix is ​​20.37%.

[0082] Example 4

[0083] The preparation method of the resin-based ceramic composite material is basically the same as that of Example 1, except that: in step (2), the boron nitride nanosheets, the barium glass powder (ceramic material) with an average particle size of 0.7 μm, and the resin monomer containing an initiator (the resin monomer is composed of urethane dimethacrylate and triethylene glycol dimethacrylate in a mass ratio of 7:3) are added to a ball mill in a mass ratio of 0.9:97:25;

[0084] In step (3), based on the mass of the resin-based ceramic composite material, the mass percentage of the boron nitride nanosheets is 0.73%, the mass percentage of the ceramic material is 78.93%, and the mass percentage of the resin matrix is ​​20.34%.

[0085] Example 5

[0086] The preparation method of the resin-based ceramic composite material is basically the same as that of Example 1, except that in step (2), the resin monomer is composed of urethane dimethacrylate and triethylene glycol dimethacrylate in a mass ratio of 6:4.

[0087] Example 6

[0088] The preparation method of the resin-based ceramic composite material is basically the same as that of Example 1, except that: in step (2), the boron nitride nanosheets, the barium glass powder (ceramic material) with an average particle size of 0.7 μm, and the resin monomer containing an initiator (the resin monomer is composed of urethane dimethacrylate and triethylene glycol dimethacrylate in a mass ratio of 6:4) are added to a ball mill in a mass ratio of 0.5:97:25;

[0089] In step (3), based on the mass of the resin-based ceramic composite material, the mass percentage of the boron nitride nanosheets is 0.41%, the mass percentage of the ceramic material is 79.18%, and the mass percentage of the resin matrix is ​​20.41%.

[0090] Example 7

[0091] The preparation method of the resin-based ceramic composite material is basically the same as that of Example 1, except that: in step (2), the boron nitride nanosheets, the barium glass powder (ceramic material) with an average particle size of 0.7 μm, and the resin monomer containing an initiator (the resin monomer is composed of urethane dimethacrylate and triethylene glycol dimethacrylate in a mass ratio of 6:4) are added to a ball mill in a mass ratio of 0.7:97:25;

[0092] In step (3), based on the mass of the resin-based ceramic composite material, the mass percentage of the boron nitride nanosheets is 0.57%, the mass percentage of the ceramic material is 79.05%, and the mass percentage of the resin matrix is ​​20.37%.

[0093] Example 8

[0094] The preparation method of the resin-based ceramic composite material is basically the same as that of Example 1, except that: in step (2), the boron nitride nanosheets, the barium glass powder (ceramic material) with an average particle size of 0.7 μm, and the resin monomer containing an initiator (the resin monomer is composed of urethane dimethacrylate and triethylene glycol dimethacrylate in a mass ratio of 6:4) are added to a ball mill in a mass ratio of 0.9:97:25;

[0095] In step (3), based on the mass of the resin-based ceramic composite material, the mass percentage of the boron nitride nanosheets is 0.73%, the mass percentage of the ceramic material is 78.93%, and the mass percentage of the resin matrix is ​​20.34%.

[0096] Example 9

[0097] The preparation method of the resin-based ceramic composite material is basically the same as that of Example 1, except that in step (2), the resin monomer is composed of urethane dimethacrylate and triethylene glycol dimethacrylate in a mass ratio of 1:1.

[0098] Example 10

[0099] The preparation method of the resin-based ceramic composite material is basically the same as that of Example 1, except that: in step (2), the boron nitride nanosheets, the barium glass powder (ceramic material) with an average particle size of 0.7 μm, and the resin monomer containing an initiator (the resin monomer is composed of urethane dimethacrylate and triethylene glycol dimethacrylate in a mass ratio of 1:1) are added to a ball mill in a mass ratio of 0.5:97:25;

[0100] In step (3), based on the mass of the resin-based ceramic composite material, the mass percentage of the boron nitride nanosheets is 0.41%, the mass percentage of the ceramic material is 79.18%, and the mass percentage of the resin matrix is ​​20.41%.

[0101] Embodiment 11

[0102] The preparation method of the resin-based ceramic composite material is basically the same as that of Example 1, except that: in step (2), the boron nitride nanosheets, the barium glass powder (ceramic material) with an average particle size of 0.7 μm, and the resin monomer containing an initiator (the resin monomer is composed of urethane dimethacrylate and triethylene glycol dimethacrylate in a mass ratio of 1:1) are added to a ball mill in a mass ratio of 0.7:97:25;

[0103] In step (3), based on the mass of the resin-based ceramic composite material, the mass percentage of the boron nitride nanosheets is 0.57%, the mass percentage of the ceramic material is 79.05%, and the mass percentage of the resin matrix is ​​20.37%.

[0104] Example 12

[0105] The preparation method of the resin-based ceramic composite material is basically the same as that of Example 1, except that: in step (2), the boron nitride nanosheets, the barium glass powder (ceramic material) with an average particle size of 0.7 μm, and the resin monomer containing an initiator (the resin monomer is composed of urethane dimethacrylate and triethylene glycol dimethacrylate in a mass ratio of 1:1) are added to a ball mill in a mass ratio of 0.9:97:25;

[0106] In step (3), based on the mass of the resin-based ceramic composite material, the mass percentage of the boron nitride nanosheets is 0.73%, the mass percentage of the ceramic material is 78.93%, and the mass percentage of the resin matrix is ​​20.34%.

[0107] Example 13

[0108] The preparation method of the resin-based ceramic composite material is basically the same as that of Example 1, except that: in step (2), the boron nitride nanosheets, the barium glass powder (ceramic material) with an average particle size of 0.7 μm, and the resin monomer containing an initiator (the resin monomer is composed of urethane dimethacrylate and triethylene glycol dimethacrylate in a mass ratio of 7:3) are added to a ball mill in a mass ratio of 0.4:97:25;

[0109] In step (3), based on the mass of the resin-based ceramic composite material, the mass percentage of the boron nitride nanosheets is 0.33%, the mass percentage of the ceramic material is 79.25%, and the mass percentage of the resin matrix is ​​20.42%.

[0110] Embodiment 14

[0111] The preparation method of the resin-based ceramic composite material is basically the same as that of Example 1, except that: in step (2), the boron nitride nanosheets, the barium glass powder (ceramic material) with an average particle size of 0.7 μm, and the resin monomer containing an initiator (the resin monomer is composed of urethane dimethacrylate and triethylene glycol dimethacrylate in a mass ratio of 7:3) are added to a ball mill in a mass ratio of 1.1:97:25;

[0112] In step (3), based on the mass of the resin-based ceramic composite material, the mass percentage of the boron nitride nanosheets is 0.89%, the mass percentage of the ceramic material is 78.80%, and the mass percentage of the resin matrix is ​​20.31%.

[0113] Embodiment 15

[0114] The preparation method of the resin-based ceramic composite material is basically the same as that of Example 1, except that: in step (2), the boron nitride nanosheets, the barium glass powder (ceramic material) with an average particle size of 0.7 μm, and the resin monomer containing an initiator (the resin monomer is composed of urethane dimethacrylate and triethylene glycol dimethacrylate in a mass ratio of 7:3) are added to a ball mill in a mass ratio of 1.2:97:25;

[0115] In step (3), based on the mass of the resin-based ceramic composite material, the mass percentage of the boron nitride nanosheets is 0.97%, the mass percentage of the ceramic material is 78.73%, and the mass percentage of the resin matrix is ​​20.29%.

[0116] Comparative Example 1

[0117] The preparation method of the resin-based ceramic composite material is basically the same as that of Example 1, except that: in step (2), barium glass powder (ceramic material) with an average particle size of 0.7 μm and a resin monomer containing an initiator (the resin monomer is composed of urethane dimethacrylate and triethylene glycol dimethacrylate in a mass ratio of 7:3) are added to a ball mill in a mass ratio of 100:25;

[0118] In step (3), based on the mass of the resin-based ceramic composite material, the mass percentage of the ceramic material is 80%, and the mass percentage of the resin matrix is ​​20%.

[0119] Comparative Example 2

[0120] The preparation method of the resin-based ceramic composite material is basically the same as that of Comparative Example 1, except that: in step (2), barium glass powder (ceramic material) with an average particle size of 0.7 μm and a resin monomer containing an initiator (the resin monomer is composed of dimethacrylate urethane and dimethacrylate triethylene glycol in a mass ratio of 6:4) are added to a ball mill in a mass ratio of 100:25.

[0121] Comparative Example 3

[0122] The preparation method of the resin-based ceramic composite material is basically the same as that of Comparative Example 1, except that: in step (2), barium glass powder (ceramic material) with an average particle size of 0.7 μm and a resin monomer containing an initiator (the resin monomer is composed of urethane dimethacrylate and triethylene glycol dimethacrylate in a mass ratio of 1:1) are added to a ball mill in a mass ratio of 100:25.

[0123] Comparative Example 4

[0124] The preparation method of the resin-based ceramic composite material is basically the same as that of Example 1, except that: in step (2), the boron nitride nanosheets, the barium glass powder (ceramic material) with an average particle size of 0.7 μm, and the resin monomer containing an initiator (the resin monomer is composed of urethane dimethacrylate and triethylene glycol dimethacrylate in a mass ratio of 7:3) are added to a ball mill in a mass ratio of 0.05:97:25;

[0125] In step (3), based on the mass of the resin-based ceramic composite material, the mass percentage of the boron nitride nanosheets is 0.04%, the mass percentage of the ceramic material is 79.48%, and the mass percentage of the resin matrix is ​​20.48%.

[0126] Comparative Example 5

[0127] The preparation method of the resin-based ceramic composite material is basically the same as that of Example 1, except that: in step (2), the boron nitride nanosheets, the barium glass powder (ceramic material) with an average particle size of 0.7 μm, and the resin monomer containing an initiator (the resin monomer is composed of urethane dimethacrylate and triethylene glycol dimethacrylate in a mass ratio of 7:3) are added to a ball mill in a mass ratio of 1.6:97:25;

[0128] In step (3), based on the mass of the resin-based ceramic composite material, the mass percentage of the boron nitride nanosheets is 1.29%, the mass percentage of the ceramic material is 78.48%, and the mass percentage of the resin matrix is ​​20.23%.

[0129] Test Case

[0130] The bending strength, Vickers hardness, bending strength and Vickers hardness after soaking in water for 7 days, and fracture toughness of the resin-based ceramic composite materials prepared in each embodiment and each comparative example were tested.

[0131] The flexural strength was tested using a universal testing machine (AGS, Shimadzu, Japan). A three-point bending test was used with a loading rate of 1 mm / min and a sample size of 18 mm × 4 mm × 2 mm. The average value of the test results of 10 samples was taken as the flexural strength of the resin-based ceramic composite material.

[0132] The hardness was tested using a Vickers hardness tester (VH1150, Wilson, USA), with a sample size of 6 mm × 3 mm × 25 mm. The average value of the test results of 10 samples was taken as the hardness of the resin-based ceramic composite material.

[0133] The resin-based ceramic composite material was made into a 17mm×4mm×3mm specimen, and a V-shaped groove was ground in the center of the lower surface of the specimen using a V-shaped notching machine. The specimen was loaded until it broke using the three-point bending test principle, and the maximum load value σ at the time of fracture was recorded, and then the fracture toughness KIc (MPa·m 1 / 2 ). The average value of the test results of 10 specimens was taken as the fracture toughness of the resin-based ceramic composite material.

[0134] The test results of each embodiment and each comparative example are shown in Table 1.

[0135] Table 1

[0136]

[0137]

[0138] It can be seen from the data in Table 1 that compared with Comparative Examples 1 to 5, the flexural strength, Vickers hardness and fracture toughness of the resin-based ceramic composite materials prepared in Examples 1 to 15 are relatively high, the Vickers hardness is between that of enamel and dentin, and the flexural strength after soaking in water for 7 days and the Vickers hardness after soaking in water for 7 days are also relatively high, indicating that by using the combination of boron nitride nanosheets, ceramic materials and resin matrix, and controlling the mass percentage of boron nitride nanosheets in the resin-based ceramic composite material to be 0.1% to 1%, the mass percentage of ceramic material to be 82% to 83%, and the mass percentage of resin matrix to be 16% to 17.9%, the flexural strength, hardness and fracture toughness of the resin-based ceramic composite material can be effectively improved, so that it can be used in the human oral environment.

[0139] By comparing Examples 1 to 4 and Examples 13 to 15, it can be seen that Examples 2 to 4 and Examples 13 to 14 control the mass percentage of boron nitride nanosheets in the resin-based ceramic composite material to be 0.3% to 0.9%, which can further improve the bending strength, hardness and fracture toughness of the composite material.

[0140] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0141] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims, and the description may be used to interpret the content of the claims.

Claims

1. A resin-based ceramic composite material, characterized in that: It includes boron nitride nanosheets, ceramic materials and a resin matrix; based on the mass of the resin-based ceramic composite material, the mass percentage of the boron nitride nanosheets is 0.1% to 1%, the mass percentage of the ceramic material is 82% to 83%, and the mass percentage of the resin matrix is ​​16% to 17.9%.

2. The resin-based ceramic composite material according to claim 1, characterized in that: Based on the mass of the resin-based ceramic composite material, the mass percentage of the boron nitride nanosheets is 0.3% to 0.9%.

3. The resin-based ceramic composite material according to claim 1, characterized in that: The average diameter of the boron nitride nanosheets is 0.1 μm to 0.4 μm.

4. The resin-based ceramic composite material according to any one of claims 1 to 3, characterized in that: The resin-based ceramic composite material has at least one of the following characteristics (1) to (3): (1) The ceramic material includes at least one of barium glass powder and silanized barium glass powder; (2) The average particle size of the ceramic material is 0.7 μm to 3 μm; (3) The resin matrix includes at least two of bisphenol A propylene glycol dimethacrylate, triethylene glycol dimethacrylate, methacrylate and urethane dimethacrylate.

5. The resin-based ceramic composite material according to claim 4, characterized in that: The resin matrix includes triethylene glycol dimethacrylate and urethane dimethacrylate, and the mass ratio of the triethylene glycol dimethacrylate to the urethane dimethacrylate is (7-3): (3-7).

6. The resin-based ceramic composite material according to any one of claims 1 to 3, characterized in that: The resin-based ceramic composite material has at least one of the following characteristics (1) to (3): (1) The flexural strength of the resin-based ceramic composite material is ≥ 209 MPa, and can be selected from 209 MPa to 245 MPa; (2) The fracture toughness of the resin-based ceramic composite material is 1.25 MPa·m 1 / 2 ~2.05 MPa·m 1 / 2 ; (3) The Vickers hardness of the resin-based ceramic composite material is ≥103HV, and can be selected from 103HV to 125HV.

7. A method for preparing a resin-based ceramic composite material, characterized in that: The steps include: The boron nitride nanosheets, ceramic materials, initiators and resin monomers are mixed and subjected to dry pressing to obtain an intermediate; The intermediate is cured so that the resin monomer forms a resin matrix to obtain a resin-based ceramic composite material; the resin-based ceramic composite material includes the boron nitride nanosheets, the ceramic material and the resin matrix; based on the mass of the resin-based ceramic composite material, the mass percentage of the boron nitride nanosheets is 0.1% to 1%, the mass percentage of the ceramic material is 82% to 83%, and the mass percentage of the resin matrix is ​​16% to 17.9%.

8. The preparation method according to claim 7, characterized in that: The preparation method satisfies at least one of the following conditions (1) to (4): (1) The mass of the initiator is 0.1wt% to 0.5wt% of the mass of the resin monomer; (2) The initiator includes one or more of a peroxide initiator and an azo compound initiator; (3) The dry pressing process includes compression molding, and the process conditions of the compression molding process include: the compression molding pressure is 10MPa~20MPa; (4) The process conditions of the curing treatment include: a curing temperature of 80°C to 140°C and a curing time of 7h to 12h.

9. The preparation method according to claim 7 or 8, characterized in that: The preparation method satisfies at least one of the following conditions (1) to (2): (1) The step of mixing the boron nitride nanosheets, the ceramic material, the initiator and the resin monomer comprises: mixing the boron nitride nanosheets, the ceramic material, the initiator, the resin monomer and the solvent by ball milling, wherein the solvent comprises an alcohol solvent; (2) Before the step of mixing the boron nitride nanosheets, the ceramic material, the initiator and the resin monomer, the method further includes: dispersing and pre-drying the boron nitride raw material to obtain the boron nitride nanosheets, wherein the dispersing treatment includes at least one of a ball milling method and an ultrasonic method.

10. Use of at least one of the resin-based ceramic composite material according to any one of claims 1 to 6 and the resin-based ceramic composite material prepared by the preparation method according to any one of claims 7 to 9 in the preparation of dental restoration products.